Improvement of polyphenol properties upon glucosylation in a UV‐induced skin cell ageing model. (29th September 2014) - Nadim, M.; Auriol, D.; Lamerant‐FayeL, N.; Lefèvre, F.; Dubanet, L.; Redziniak, G.; Kieda, C.; Grillon, C.
Synopsis: Objective: Polyphenols are strong antioxidant molecules allowing prevention of skin photo‐ageing damages, but their use is limited due to low solubility and toxicity towards skin cells. We postulated that enzymatic glucosylation could improve their solubility, stability and, consequently, their efficacy. The aim of this work was to study changes induced by addition of a glucose moiety on two polyphenols displaying very different chemical structures [caffeic acid (CA), epigallocatechin‐3‐gallate (EGCG) and there glucosylated form, Glc‐CA and Glc‐EGCG] by assessing their cytotoxic properties and their antioxidant and anti‐inflammatory activities. Methods: Their antioxidant effect was assessed first by the classical DPPH radical‐scavenging method. Then, a panel of human skin cells (keratinocytes, melanocytes, fibroblasts and endothelial cells) was used to evaluate their effect on cell toxicity and their antioxidant activities. With this aim, a photo‐ageing model based on UV irradiation of skin cells was established. Molecule activity was assessed on reactive oxygen species (ROS) production, on superoxide dismutase (SOD) and catalase activities and, finally, on inflammatory factor production IL‐6, IL‐8 and IL‐1β. Results: In an acellular model, antioxidant activity assessed by DPPH method was strongly reduced for Glc‐CA compared to CA, whereas it remained the same for Glc‐EGCG compared to EGCG. Glucosylated derivatives did not display more toxic effect on various skin cells. Moreover, toxicity was even strongly reduced for caffeic acid upon glucosylation. The efficacy of glucosyl‐compounds against UV‐induced ROS production was preserved, both with pre‐ and post‐UV treatments. Particularly, a better antioxidant efficacy was shown by Glc‐EGCG, vs. EGCG, on keratinocytes. In addition, an induction of SOD and catalase activity was clearly observed for Glc‐CA. Both glucosyl‐polyphenols display the same activity as their parent molecule in decreasing inflammatory factor production. Conclusion: Our results demonstrated that enzymatic glucosylation of CA and EGCG led to an improved or preserved antioxidant activity in a cellular model of UV‐induced skin ageing, despite the decrease in instantaneous antioxidant properties observed for Glc‐CA. Glc‐EGCG is specifically more active on keratinocytes, suggesting a specific targeting. Such glucosylated polyphenols displaying improved physicochemical and biological properties should be better candidates than natural ones for use in food additives and cosmetics.